Pentingnya Marketing Media Sosial pada UMKM Desa Cibeber, Purwakarta, Jawa Barat - Anissa, Anissa; Irfal, Irfal; Tarigan, Emenina (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan Digital, 2026)
This study aims to explore the importance of social media marketing for micro, small, and medium-sized enterprises (MSMEs) in Cibeber Village, Purwakarta, West Java, with a particular focus on social media utilization, perceived benefits, customer interaction, content development, and challenges in its implementation. This study employed a descriptive qualitative approach. Data were collected through in-depth interviews, observations, and documentation involving MSME actors in Cibeber Village and were analyzed using thematic analysis. The findings indicate that social media is considered an important promotional tool for expanding market reach, increasing product visibility, facilitating communication with customers, and strengthening customer relationships. Social media also provides opportunities for MSMEs to integrate product promotion with the tourism potential and local identity of Cibeber Village. However, optimizing social media utilization remains constrained by limited digital literacy, content creation skills, understanding of digital marketing strategies, and access to technological resources and support. Therefore, the effectiveness of social media marketing is determined not only by access to digital platforms but also by the ability of MSME actors to manage and integrate social media strategically into their marketing activities. Keywords: social media marketing, MSMEs, digital transformation, tourism village